Assessment of Radiological Status for the Destroyed Nuclear Fuel Fabrication Facility at AL-Tuwaitha Site - Yousif M. Zayir Al-Bakhat; Hussein J. Mugar; Qusay A. Abdulhadi; Nabeel H. Ameen; Fouzey H. Kitah; Mohammed Adel Jawad; Hassan M. Ali (Journal of Madenat Alelem University College, 2014)
The fuel fabrication facility (FFF) is one of the destroyed nuclear facilities in AL-Tuwaitha site that requires remediation and decommissioning. The characterization of activities of FFF had been conducted in 2013 using hand-held radiation detection instruments for the structures and the surface of FFF for contaminations. The exposure dose rates and laboratory measurement was conducted for forty nine soil samples that collected for activity measurements and analysis using gamma spectrometry technique of high purity germanium detector. The surveys and laboratory results indicated that the FFF was contaminated with uranium-238 and uranium-235 nuclides in excess of the IAEA limits for exemption from regulatory control, and indicating that the decommissioning operations for the FFF must be subjected to regulatory control and safety surveillance to ensure adequate protection of the operators, public and the environment during implementation of the decommissioning operations, according to ALARA (As Low As Reasonable Achievable) principle as recommended by International Atomic Energy Agency (IAEA).